Analysis of Students' Mathematical Problem Solving Ability Based on Learning Interest - Purba, Novi Wulandari; Hasanah, Rusi Ulfa (Unnes Journal of Mathematics Education, 2023)
This research aimed to describe the ability to solve mathematical problems based on learning interests. The method used in this research was qualitative descriptive research. The research subjects were class X1 MIA 1 SMA Kartika 1-4 Pematang Siantar students. The selection of research subjects used a purposive sampling technique. The research instruments in this study were learning interest questionnaires, tests of mathematical problem solving abilities and interview guidelines. The data analysis technique used in this study was data reduction, data presentation, and drawing conclusions. The results show that subject student S30 with high learning interest can fulfill all indicators of mathematical problem solving abilities, including understanding problems, making solving plans, doing calculations, and re-checking the results obtained. Subject student S18 with moderate learning interest can fulfill the four indicators of problem solving ability, but the student is less able to plan problem solving, implement plans, and re-examine the results obtained. Subject student S2 with low learning interest can only meet the indicators of understanding the problem.